Optimal delegation contract with portfolio risk - Sheng, Jiliang; Yang, Yanyan; Yang, Jun (Journal of Banking & Finance, 2025)
Conventional linear benchmarked contracts tend to cause excessive pegging to the benchmark and thus price distortion of stocks in the benchmark. This paper studies the optimal delegation contract when there is principal-agent friction. Specifically, it explores the impacts of incorporating the risk of invested portfolio in the contract on optimal strategies of the principal and the agent as well as on equilibrium asset prices. When agency friction is severe, the optimal contract provides rewards for portfolio risk to improve risk sharing and grants compensation for index return to propel the agent to deviate from pegging to index. In equilibrium, the principal conducts index investment while the agent invests only in individual risky assets, and price distortion caused by agency friction is mitigated.